The Effectiveness of the Cognitive Behavior Modification Approach with Group Settings to Reduce Students Cheating Behavior at SMA Negeri 8 Padang - Lastri Anita; Yeni Karneli (Jurnal Neo Konseling, 2019)
Cheating behavior is cheating behavior, dishonest and does not obey the rules carried out by individuals without thinking about the impact on themselves by giving answers to friends, looking at friends' answers, throwing papers and giving answer codes to friends. This research aims to (1) describe cheating behavior of students in SMA Negeri 8 Padang, (2) describe the cognitive behavior modification (CBM) approach to reduce student cheating behavior, (3) test the effectiveness of the CBM approach effectively reducing student cheating behavior. This study uses an experimental design of a pre-experimental model, using the design of The One Group Pretest Posttest Designt. The subjects in this study were 10 students of SMA Negeri 8 Padang class XI IPS 1. The data collection tool used was a questionnaire. Data analysis techniques used Wilcoxon signed range test design data analysis. The results showed that the CBM approach was effective in reducing student cheating behavior with 76.4% pretest results in the high category and 40.4% posttest in the low category. This study gives meaning that the Cognitive Behaviour Modification approach is able to reduce student cheating behavior, for that Guidance and Counseling teachers need to apply this approach in caryying out counseling services to students.